Accessory Mineral Behaviour in Granulite Migmatites: a Case Study from the Kerala Khondalite Belt, India. (24th September 2014) - Harley, Simon L.; Nandakumar, V.
Abstract: Zircon, monazite, garnet and feldspar trace element microanalysis, zircon and monazite U–Pb isotopic ages and monazite Th–U–Pb chemical dating, determined in situ from a leucogranitic vein in migmatitic gneiss at Kulappara in the Kerala Khondalite Belt (Trivandrum Block), India, demonstrate accessory mineral crystallization from an evolving melt-bearing system from c. 545 to 535 Ma at temperatures of greater than 780°C. Marked changes in zircon chemistry to lower Th/U and Ybn /Gdn occurred during its growth in the evolving melt, correlated with a dramatic change in microtexture from initial 'hopper'-like feathered-core and outer planar sector domains to darker planar zones and elliptical to lobate infilling and replacement zircon. Initially high Th/U, high heavy rare earth element (HREE) zircon crystallized rapidly from melt from 544 ± 9 Ma under open-system conditions in which the host-rock mineralogy had no chemical impact. This zircon precipitated prior to crystallization of significant garnet, trapping melt as inclusions that later crystallized to cryptogranite within zircon cores. Further zircon crystallization ensued under localized closed-system conditions leading to the establishment of zircon–garnet REE equilibrium at least on local (i.e. millimetre to centimetre) scales, consistent with melt entrapment, at 542 ± 6 Ma. Monazite crystallized in this fractionated melt by 535 ± 6 Ma. These results demonstrate that zircon can be a sensitive indicator of changing conditions and scales of melt transfer and interaction in high-temperature migmatites, recording in this instance a transition from melt-dominated open-system behaviour to closed-system crystallization and mineral–melt interaction at T > 780°C in the deep crust of a hot orogenic belt.